2016
DOI: 10.1212/wnl.0000000000002675
|View full text |Cite
|
Sign up to set email alerts
|

Predicting motor improvement after stroke with clinical assessment and diffusion tensor imaging

Abstract: Reliable predictors of motor improvement in individual patients after stroke are scarce. Acute determination of upper limb Fugl-Meyer assessment (FMA) appears to have predictive value.1,2 This approach predicts that patients will improve approximately 70% of the difference between the maximum upper extremity FMA score and the score first tested for a given individual (recoverytypical). However, a significant subset of patients improves much less than predicted (recovery-atypical). Alternative models using othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 7 publications
(6 reference statements)
10
86
1
2
Order By: Relevance
“…First, repair mechanisms seem to have an intrinsic capacity to recover about 70% of lost functions. The same proportion has been demonstrated in previous studies for motor and language recovery in patients in the PROP group. The present study confirms the same rule for recovery from neglect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, repair mechanisms seem to have an intrinsic capacity to recover about 70% of lost functions. The same proportion has been demonstrated in previous studies for motor and language recovery in patients in the PROP group. The present study confirms the same rule for recovery from neglect.…”
Section: Discussionsupporting
confidence: 89%
“…Second, under some circumstances, the intrinsic repair mechanisms appear to remain inefficient in a subset of severely affected patients. In the case of motor function, this occurs in patients with severe disruption of the cortico‐spinal tract . Here, we demonstrate the same dichotomy for aphasia and neglect.…”
Section: Discussionsupporting
confidence: 66%
“…A premise of studies that use neurophysiology and neuroimaging data to predict arm recovery is that clinical data alone do not provide adequate predictions of arm recovery, particularly in patients with initial severe arm impairment [73,103,108,109]. When this claim is made explicitly it is often supported by reference to the proportional recovery model or poorly conducted prognostic studies, rather than models which have shown good predictive accuracy [25,42].…”
Section: Arm Recovery: Do Neurophysiological and Neuroimaging Datamentioning
confidence: 99%
“…MRI can also be used to derive biomarkers of the motor system after stroke 10. Worse upper limb motor recovery and outcomes are predicted by greater stroke lesion load on descending corticomotor pathways,11 and greater asymmetry in fractional anisotropy along the corticospinal tracts 12, 13, 14, 15. To date no single clinical measure or neurological biomarker has been able to accurately predict motor recovery or outcome for all patients, and therefore approaches using combinations of measures and biomarkers are needed 6…”
Section: Introductionmentioning
confidence: 99%